Australia's signing of the Artemis Accords: a positive development or a controversial choice?. Issue 3 (4th May 2021) - Tronchetti, Fabio; Liu, Hao
ABSTRACT: On 15 October 2020, Australia signed the US Artemis Accords. Such a move was heralded as an important step towards promoting the Australian space program and enabling the country to take part in an ambitious space exploration venture. While not denying the importance of such a move, the present commentary analyzes it in a critical manner by assessing its legal and diplomatic implications. Taking into account Australia's prior membership of the 1979 Moon Agreement and the discrepancies that exists between the Agreement's provisions and those of the Artemis Accords, the present commentary not only views Australia's simultaneous membership of both instruments as problematic but also considers it not sustainable in the long term. Based on these considerations, this commentary recommends Australia to either reconsider its membership to the Moon Agreement or, at least, to clarify how the two instruments may co-exists from a legal and political perspective.